DAMPAK KONFLIK PERAN GANDA DAN STRES KERJA TERHADAP MOTIVASI DAN KOMITMEN DOSEN WANITA PEJABAT STRUKTURAL - ALIFIULAHTIN UTAMININGSIH (STIE Indonesia Malang, 2019)
The aims of research is to know multiple role conflict and work stress structural woman lecturer at Islamic State University of Malang. The study analysed of gender and feminism theory and multiple role conflict, motivation and organizational commitment. The research methode is use kualitatif descriptif. The informan are all of structural woman lecturer at Islamic University of Malang at top, midle and lower management. The main data is collected by interview. Data analysis use kualitatif method to explain and answer research problem to describe comprehenshifly to explain about problem of multiple role conflict and works stress them. The effect from those problem caused work stress because presure at along time at office in order to family timeless, but the motivation highly because they asumtion work is religiusly and those effect highly of affective commitment. Key words: multiple role conflict, work stress, motivation and organizational commitment.